Molecular characterization and diversity analysis of Brassica genotypes - Rahman, MM; Rahman, MM; Rahman, L; Begum, H; Islam, SMM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 1-8